Pull-out strength of post-installed connectors in thin UHPC members. (December 2022) - Prejs, Andy; Jawdhari, Akram; Fam, Amir
Abstract: Ultra-high-performance concrete (UHPC) has recently been introduced to the precast industry in the form of thin components such as the insulated double wythe precast concrete (DWPC) panels. Existing connectors for conventional DWPC panels may not be applicable for the very thin UHPC-DWPC panels. This paper presents an experimental campaign investigating the behavior and design of screw anchors and a newly designed threaded rod connector embedded in thin UHPC members under pull-out forces. The parameters examined are concrete thickness ( t c ), connector diameter ( d ), fiber percentage in UHPC ( p f ), embedment depth ( h e f ), support ring diameter ( d s ) of the slab, and concrete compressive strength ( f' c ). The failure modes consisted of concrete breakout, radial cracking, or a combination of the two. The threaded rod demonstrated better structural performance, with ultimate pull-out loads ( P u ) 20 to 50% greater than the screw anchor. Increasing the embedment depth from 0.75 t c to 1.0 t c (full embedment) increased P u on average by 19% and 67% for the screw anchor in 25 and 38 mm thick slabs, respectively. Increasing slab thickness from 15 to 38 mm, with 1.0 t c embedment, resulted in P u to be on average over 3.5 and 4 times greater for the screw anchor and threaded rod, respectively. Results showed that connector diameter, fiber percentage, and support ring size did not have significant effect on P u . Two existing models were evaluated and were found to over-estimate the pull-out capacity based on the parameters of the study. A regression analysis was performed on the data and two new design equations were developed to predict the pull-out capacity of each connector with a high degree of accuracy. A design case study is also presented. Highlights: Reduced thickness of UHPC member increases vulnerability to connectors pull-out. Study examined effect of critical parameters on pull-out strength (Pu) of 2 types of connectors. Threaded rod connector bearing on back side showed 20%–50% greater Pu than screw anchor. Two existing models were found to grossly over-estimate Pu. Regression analysis was performed on the data and new design equations were developed.